Mouse was mad - Urban, Linda; Cole, Henry, 1955- (New York : Harcourt Children's Books, 2009)
Mouse struggles to find the right way to express his anger, modeling the behavior of Hare, Bear, Hedgehog, and Bobcat, only to discover that his own way may be the best way of all.
1.6
K-3
Keywords: Anger -- Juvenile fiction; Animals -- Juvenile fiction; Individuality -- Juvenile fiction; Mice -- Juvenile fiction; Anger -- Fiction; Animals -- Fiction; Individuality -- Fiction; Mice -- Fiction; Anger -- Fiction; Animals -- Fiction; Individuality -- Fiction; Mice -- Fiction